Analisis Perlakuan Akuntansi Persediaan Obat-Obatan Pada Apotek Rumah Sakit Jiwa Kendari Provinsi Sulawesi Tenggara - Teti Alvia, Ilham Akbar Garusu, Muhammad Fathir Maulid Yusuf (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
The problem in this research is how the system of recording, valuing and disclosing inventory at Kendari Mental Hospital Southeast Sulawesi Province is based on the Statement of Inventory Accounting Standards (PSAP No.05). The purpose of this study was to determine the Accounting Inventory Treatment of Medicines referred to in PSAP No.05. Based on the results of the study, it shows that the Kendari Mental Hospital Southeast Sulawesi Province uses the perpetual method for recording inventory and the First In First Out (FIFO) method for valuing inventories. From the results of the study showed that there were differences in the amount of ending inventory of medicines according to the company according to the author's calculation. This difference is caused by the existence of an irregular recording so that the effect is there are several purchase transactions, and sales transactions that are not recorded. From the research, Kendari Mental Hospital Southeast Sulawesi Province has applied inventory accounting standards but not yet fully in accordance with PSAP No.05. The recommendation is that hospitals should record inventory regularly and consistently with merchandise supplies coming in and going out, so as to minimize the possibility of recording errors or transactions that are not recorded.